2018
DOI: 10.24996/ijs.2018.59.1a.5
|View full text |Cite
|
Sign up to set email alerts
|

Study Antibacterial Activity of Honey Against Some Common Species of Pathogenic Bacteria

Abstract: Honey is one of the most products has been used as an antimicrobial agent since the ancient times. The potential antimicrobial activity of honey is arise from its physiochemical proprieties such as high osmotic pressure, low pH, in addition to other factors and enzymes that work as antimicrobial agents. All these components and characteristics of honey led to consider it as one of the most efficient, useful and natural antimicrobial agents. From this point of view, recent study aim to evaluate the antibacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Recent studies have shown a growing interest in the physiochemical parameters of honey obtained from different species of bees. In a study conducted by Al-Hasani (2018) [1] , the antimicrobial properties of honey were emphasized, with its effectiveness attributed to specific physiochemical characteristics like high osmotic pressure and low pH. Wu et al, 2020 [76] analyzed the physicochemical parameters, like sugar content, minerals, and volatile compounds as main factors for the evaluation of multifloral honey obtained from Apis cerana cerana Fabricius, Apis dorsata Fabricius, and Lepidotrigona flavibasis Cockerell.…”
Section: Properties Of Honeymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown a growing interest in the physiochemical parameters of honey obtained from different species of bees. In a study conducted by Al-Hasani (2018) [1] , the antimicrobial properties of honey were emphasized, with its effectiveness attributed to specific physiochemical characteristics like high osmotic pressure and low pH. Wu et al, 2020 [76] analyzed the physicochemical parameters, like sugar content, minerals, and volatile compounds as main factors for the evaluation of multifloral honey obtained from Apis cerana cerana Fabricius, Apis dorsata Fabricius, and Lepidotrigona flavibasis Cockerell.…”
Section: Properties Of Honeymentioning
confidence: 99%
“…From pollination to different bee products like wax, honey, royal jelly, propolis, and pollen, an important role is played by the bees in maintaining the ecosystem. The Codex Alimentarius Commission (2001) [1] , describes honey as a sugary substance created by honeybees using nectar or various secretions found on living plants. The bees gather, alter, and store this substance in honeycombs.…”
Section: Introductionmentioning
confidence: 99%
“…The results of in vitro evaluation of antibacterial activity for local and imported honey samples in the presence of Gram+ and Gram -bacteria by the diffusion method in agar media are summarized in Table 4 below. Al-Hasani (2018) have shown that diameters of inhibiting areas in bacteria diminish gradually as honey concentrations drop. Sidi Achour 100% pure honey had an inhibiting action 6.33 ± 0.57 6.00 ± 0.00 6.00 ± 0.00 7.33 ± 2.30 Bacillus cereus ATCC 11778 6.00 ± 0.00 6.66 ± 1.15 6.00 ± 0.00 6.00 ± 0.00 Enterococcus faecalis 7.33 ± 2.30 7.66 ± 2.88 6.00 ± 0.00 6.00 ± 0.00 on the growth of all the tested strains, this inhibitive action was observed at 75% concentration of the same honey on Escherichia coli, Salmonella enteritidis, Staphylococcus aureus and Enterococcus faecalis, except Bacillus cereus (9.33 ± 4.71 mm).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Hamed et al [8] focused to determination of water-soluble vitamins of Bcomplex group in Iraqi honeys by HPLC method. Al-Hasani et al [9] detected antibacterial effect of Iraqi honey samples against gram-positive and gram-negative bacteria at concentration of 100 % and the inhibition effect of honey decreased as honey diluted. Abu-Almaaly [10] focused on identification of some heavy metals in samples of Iraqi honeys by atomic absorption technique.…”
Section: Introductionmentioning
confidence: 99%